Enhanced cellular uptake efficiency of DCM probes or SN38 conjugating with phenylboronic acids. Issue 7 (1st April 2020) - Zhang, Qiumeng; Che, Rui; Lu, Wei
Graphical abstract: Abstract: High-level of sialic acid (SA) expression on the surface of cancer cells is observed extremely common. Phenylboronic acids (PBAs) have a high affinity with SA. The cellular uptake efficiency could be enhanced by the strategy of introducing PBA fragments to the compounds. In this work, we synthesized five new probes with the Dicyanomethylene-4H-pyran (DCM) fluorophore, three of them conjugated with different phenylboronic acid fragments. By cellular uptake experiments, DLCB and DLAB showed enhanced cellular uptake abilities compared with DLN and DLO. These two effective phenylboronic acid fragments were then conjugated with SN-38 and the conjugates showed enhanced cellular uptake abilities by 3-fold or 7-fold compared with irinotecan. In summary, the strategy of introducing 4-carboxyphenylboronic acid and 3-amino-benzoxaborole groups shows great potential in drug delivery system. Moreover, the released linkers between boric acid and drugs deserve further studies.